Potential Role of Plant Growth Regulators in Administering Crucial Processes Against Abiotic Stresses - Sabagh, Ayman EL; Mbarki, Sonia; Hossain, Akbar; Iqbal, Muhammad Aamir; Islam, Mohammad Sohidul; Raza, Ali; Llanes, Analía; Reginato, Mariana; Rahman, Md Atikur; Mahboob, Wajid; Singhal, Rajesh Kumar; Kumari, Arpna; et al. (Frontiers in Agronomy, 2021)
Plant growth regulators (PGRs) triggernumerous metabolic and other vital plant physiological processes involved in the growth and development of plants. Under changing climate, numerious biotic and abiotic stresses hamper seed germination, seedling growth and plants development leading to decline in economic yield. However, PGRs can potentially play a direct role in regulating plant responses to various abiotic stresses and hence contribute toplant adaptation and imitation under advese environemnts. The dominant effects of abiotic stressesare growth and yield disturbance, and both these effects aredirectly overseen by the PGRs. The PGRs such as abscisic acid (ABA), salicylic acid (SA), ethylene (ET), and jasmonates (JAs) are connected to boosting plants' response to several stresses. In contrast, the PGRs including cytokinins (CKs), gibberellins (GAs), auxin, and relatively novel PGRs such as strigolactones (SLs) and brassinosteroids (BRs) are involved in plant growth and development under normal or stressful environments. In addition, polyamines, although not considered as phytohormones, but have been included in this chapter because weanticipated these as a new group of PGRs involved in several plant processes and stress responses. This chapter provides an overview of the recent advances pertaining to PGRs in boosting plants' tolerance against abiotic stresses along with highlights research gaps regarding underlying mechanisms of PGRs biosynthesis under stresses and their roles in imparting tolerance against adverse effects of suboptimal growth conditions.